KEKUATAN HUKUM GROSSE AKTA NOTARIS SEBAGAI BENTUK SURAT AUTENTIK - Oktaviana, Selvia (Lampung University)
Grosse certificates as a form letter is authentic deed that has a distinctive shape. The parties made an agreement in the form of grosse deed will be protected by law, because basically the purpose or rationale for creating grosse deed is to protect the lender in case of default and because of the executorial title.Â Keywords: Grosse of Deed, Letter Authentic, Notary